Phosphorus dynamics in litter–soil systems during litter decomposition in larch plantations across the chronosequence - Chi, Guangyu; Zeng, Fanpeng; Wang, Yang; Chen, Xin (Frontiers in Plant Science, 2022)
The dynamics of phosphorus (P) in litter-soil systems during litter decomposition across a plantation chronosequence remain to be under-investigated, especially in terms of the nutrient cycle in plantations. In this study, the P dynamics in a litter-soil system of larch (Larix kaempferi) plantations at three stand ages (10, 25 and 50 years old) were examined through a four-yr in situ decomposition experiment (experiment 1) and a 360-day indoor incubation experiment (experiment 2). The aim of experiment 1 and experiment 2 is to determine the P dynamics in litter and soil, respectively. The results in experiment 1 suggested that litter mass retained 34.1-42.5% of the initial mass after a four-yr decomposition period, and the turnover time (t0.95) of the decomposition was 11.3, 13.9 and 11.8 years for 10-, 25- and 50-year-old stand larch plantations, respectively. Litter exhibited a net P decrease during the first 180 days, followed by a phase of net P increase. The lowest P accumulation rate was found in the 25-year-old stand during the P immobilization stage. This immobilization phase was followed by a slow litter P decrease. Highly correlated relations were found between the litter decomposition rate and the initial litter N concentration and C/N, while the P accumulation rate was noticeably correlated with the initial litter P and C/P. The results in experiment 2 showed that litter addition promoted the accumulation of the highly-labile-P (Resin-P, NaHCO3-Pi and Po), as well as moderately-labile-Pi (NaOH-Pi) in the soil. The findings obtained suggest that soil microbial biomass P (MBP) and acid phosphatase activity (APA) were the primary factors driving the activation of soil P during litter decomposition. These findings would be beneficial to the systematic understanding of the nutrient cycle in plant-soil systems and litter management during the development of larch plantations.